OsPM1 is a positive regulator of rice tolerance to drought stress but a negative regulator of rice tolerance to salt stress. Issue 1 (1st January 2021) - Wang, Wei; Quan, Changqian; Zheng, Shiwei; Wang, Yu Wei; Mo, Yuhan; Ma, Chuan; Xu, Zhengjun; Li, Lihua; Huang, Zhengjian; Jia, Xiaomei; Ye, Xiaoying; Zhu, Jianqing; et al.
ABSTRACT: To understand stress response mechanisms, a multiple stress-responsive gene OsPM1 with a disordered region containing about 30 amino acid residues was screened by microarray. Promoter region analysis using PlantCARE showed this gene contains multiple cis-regulatory elements responding to abiotic stresses. Quantitative real-time PCR and promoter-GUS transgenic plant analysis verified that OsPM1 was induced by multiple abiotic stresses. OsPM1 -GFP fusion protein expression showed that OsPM1 was localized at the cell membrane. The rice plants overexpressing OsPM1 exhibited hypersensitivity to salt stress but enhanced drought tolerance compared to the wild-type plants; the rice plants expressing antisense of OsPM1 were hyposensitive to salt stress but with weak drought tolerance compared to the wild-type plants. These results showed OsPM1 is a positive regulator of rice tolerance to drought, but it's also a negative regulator of rice tolerance to salt.